Employees working with electric blasting cap shells at Hercules Port Ewen plant - Hercules Incorporated (1955)
General view of employees removing loaded blasting cap shells from trays and transferring them to racks for final assembly at the Hercules Powder Company plant in Port Ewen, New York. The individuals in the photograph are identified as follows (left to right): Robert Palen; John Schussler; and Leo Miller. Formed in 1912 as part of an anti-trust settlement with DuPont, the Hercules Powder Company (later Hercules Inc.) specialized in the manufacture of explosives and smokeless powders. The company's Port Ewen plant produced a range of special detonators designed for military use, as well as construction jobs that required blasts of dynamite, such as the clearing of quarries, mines, and tunnels.
Keywords: Detonators; Employees; Chemical industry; Propellants; Hercules Incorporated; Corporations; Explosives; Palen, Robert; Schussler, John; Miller, Leo